Economic analysis of inefficiency in wheat production: An empirical study from India - Verma, Parul; Kaur, Harpreet (Asian Development Policy Review, 2024)
The study undertook an effort to trace the production inefficiency between different farm sizes (i.e., marginal, small, semi-medium, and medium farms) for wheat crops in Uttar Pradesh, India. Using a sample of 320 farmers from the U.P., the study employed the stochastic production frontier (SPF) approach to determine the level of inefficiency using key inputs such as land, irrigation, fertilizer, seed, pesticides, equipment, and labour. Further, factors such as age, farm size (FS), soil fertility problem (SFP), awareness spearheaded by the panchayat (ASP), inaccessibility to certify seeds (ICS), and Simmons land fragmentation index (LFI) that accounted for inefficiency among various farm sizes have been taken into account. The study found that the inefficiency factors used in the study are hindering wheat production. The study exhibits significant differences among farm-wise inefficiency in Uttar Pradesh and therefore suggests the possibility of increasing the production of wheat crops in the state. The study recognizes that for farms with above-two-hectare land, production is relatively higher as compared to small and marginal farms’ production. Thus, farms above 2 hectares are, in real terms, recognised as true economic holdings in the study, as they are less inefficient relative to others. The study suggests policy measures to improve the symmetrical information regarding input usages and interventions to reduce marginalisation in the state.